Two hundred times enhancement of emission intensity of a heptadentate acyclic sensor coordinated with Zn2+ ion: synthesis, crystal structure and emission properties. Issue 11 (2nd June 2020) - Hens, Amar
Abstract: A heptadentate N 4 O 3 coordinated dinuclear zinc complex was synthesized. The sensor functioned as a "turn-on" fluorescence receptor only to Zn 2+ ion in 3:2 v/v MeOH/water in HEPES buffer at pH 7.2 at 25 °C. A huge increase in emission intensity (approximately 200 times) of the ligand was observed in the presence of Zn 2+ which was accounted for by the formation of a metal-ligand complex and thus could be used as zinc ion-selective luminescent probe, continuously emitting blue light in the presence of a UV lamp. The theoretically optimized geometry in solution state gives an idea about bond relaxation as well as change the geometric scenario of the coordinated metal ion from trigonal bipyramidal to square pyramidal. Graphical Abstract: